2015
DOI: 10.3233/jad-150298
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Tau Interactions with Endoplasmic Reticulum Proteins in Alzheimer’s Disease Brain

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder that is pathologically characterized by the formation of extracellular amyloid plaques and intraneuronal tau tangles. We recently identified that tau associates with proteins known to participate in endoplasmic reticulum (ER)-associated degradation (ERAD); consequently, ERAD becomes dysfunctional and causes neurotoxicity. We hypothesized that tau associates with other ER proteins, and that this association could also lead to cellular dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 72 publications
1
51
0
Order By: Relevance
“…Notably, it has been shown that increased levels of pathological tau lowers protein synthesis in vitro and in vivo (Meier et al, 2016). Over-expression of P301L mutant tau in rTg4510 mice upregulates the stress kinase PERK, leading to eIF2α phosphorylation, translation inhibition, and synapse loss (Meier et al, 2015; Vanderweyde et al, 2016). Inhibition of PERK ameliorates these deficits (Vanderweyde et al, 2016).…”
Section: How Do Rnp Granules Transition From a Healthy To Pathologicamentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, it has been shown that increased levels of pathological tau lowers protein synthesis in vitro and in vivo (Meier et al, 2016). Over-expression of P301L mutant tau in rTg4510 mice upregulates the stress kinase PERK, leading to eIF2α phosphorylation, translation inhibition, and synapse loss (Meier et al, 2015; Vanderweyde et al, 2016). Inhibition of PERK ameliorates these deficits (Vanderweyde et al, 2016).…”
Section: How Do Rnp Granules Transition From a Healthy To Pathologicamentioning
confidence: 99%
“…RBPs in complex with Tau and TIA1 include TAF15 and EWSR1. (5) TIA1 mediates interaction of stress granules with insoluble tau aggregates internalized from the cytoplasm (Meier et al, 2015; Brunello et al, 2016; Vanderweyde et al, 2016). …”
Section: How Do Rnp Granules Transition From a Healthy To Pathologicamentioning
confidence: 99%
“…In this environment, functional tau translocates from the cytosol to the nucleus, however tau oligomer formation appears to both inhibit the movement of protective tau to the nucleus and lead to the buildup of nuclear tau aggregates(Violet et al , 2015). Tau may also differentially interact with RNA in disease states in the endoplasmic reticulum (ER) as tau has been shown to be associated with ribosomal and other ER proteins(Meier, 2015). The redistribution of tau protein may also underlie synaptic dysfunction seen in tauopathies as tau aggregates have been found in higher proportions in the somatodendritic compartment and can be specifically detected at the pre- and post-synaptic densities in disease states(Meyer et al , 2014).…”
Section: Tau Oligomeric Strainsmentioning
confidence: 99%
“…proteomics studied revealed that Tau fibrils establish new abnormal interactions with either the insoluble proteome (Donovan et al, 2012) or ERassociated protein complexes (Meier et al, 2015). We recently showed that toxicity of an aggregation-prone variant of the protein Axin is caused by aberrant interactions established by oligomeric nano-aggregates formed in the cytoplasm (Anvarian et al, 2016).…”
Section: Previousmentioning
confidence: 99%
“…Our experimental setup focuses on the soluble fraction of the cytoplasm, the environment where fibrils naturally accumulate during the progression of Alzheimer (Wang and Mandelkow, 2016). Proteomics studies concerning Tau fibrils reveal interactomes of insoluble membrane-enriched fractions copelleted with Tau fibrils and their ER-associated components (Donovan et al, 2012;Meier et al, 2015). Here we provide data sets revealing interactions of Tau fibrils with the soluble components of the brain, to which the protein is exposed when aggregating in disease.…”
Section: Tau Fibrils Target Rna Cytoskeletal and Phosphorylation Dynmentioning
confidence: 99%